State’s Role Against Cyber Crime: Maintaining Democracy and Political Integrity - Muhammad Ruslan Afandi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The advancement of digital technology has fundamentally changed both the opportunities and vulnerabilities in the landscape of Indonesian democracy. This study examines the dual challenges posed by cybercrime and the role of the state in maintaining political integrity in the digital era. Using a qualitative case study approach, this research analyzes trends in cyberattacks targeting the democratic process, the proliferation of political disinformation, and the systematic responses undertaken by Indonesian government institutions. Data were obtained from academic literature, government reports, legal documents, and media studies, and then analyzed using thematic analysis. The findings indicate that cybercrime, ranging from attacks on election infrastructure to large-scale disinformation campaigns, poses a significant threat to public trust and the legitimacy of democratic institutions. The Indonesian government is responding with a multifaceted strategy, including regulatory reforms, the development of cybersecurity infrastructure, digital literacy initiatives, and cross-sector collaboration. However, challenges such as limited resources, inter-agency coordination, and public engagement continue to be faced. This study enriches the discourse on digital democracy by illustrating the complex interaction between technological threats and institutional resilience, and affirming the relevance of network society theory and public space in understanding Indonesia's efforts to maintain democratic integrity in the digital era.